Karchowicka Biblia Pauperum źródłem dla poznania kultury materialnej - Przybyłok, Arkadiusz (Acta Universitatis Lodziensis. Folia Archaeologica, 2017)
In 2007, there was a discovery made in st Catherine of Alexandria church in Karchowice – a wall paintings showing scenes known from New Testament. Explorers dated them widely to 15th century but analysis of the armament and clothes restricts this dating to the end of the century. All of the biblical figures (Jesus, Apostoles and women) are wearing stylised long clothes, not similar to the fashion of that medieval time, however, torturers are dressed in a typical late 15th century way. They have over-ankle shoes, tight fitting hoses and doublets some of which have also puffed sleeves. Few of them are wearing robes with fancy cuts on the edges. The most interesting piece of cloth depicted on the paintings is the one made of a textile with tile-shaped pattern or peacock’s feathers on it. There are not only civilians on the paintings but soldiers as well. Most of their armament is reduced to few elemnents only (eg. helmet and kind of weapon), but some of soldiers are wearing full plate armours with decorative garments put on them. The most popular type of helmets here is a skull cap and ball shaped kettle hat. One of the soldiers has epaulieres with pteruges which probably should be taken as an indication of painter’s imagination. The way all figures have been depicted on the wall paintings in Karchowice seems to be premeditated. While Jesus and people around him are wearing simple clothes, Romes are dressed very excessively. Thanks to that it was possible for the illiterate viewer to distinguish which of persons on the fresco is a good or a bad one.